2019
DOI: 10.1186/s12906-019-2696-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyathea gigantea (Cyatheaceae) as an antimicrobial agent against multidrug resistant organisms

Abstract: BackgroundRapid emergence of multidrug resistant (MDR) organisms in hospital and community settings often result into treatment failure, thus leading the clinicians with fewer treatment options. Cyathea gigantea, an ethnomedicinally important fern used in cuts and wound infections. So, if this medicinal plant is used in treating the MDR infections then it might bring certain relief in future treatment options.MethodsAntibacterial activity of C. gigantea against MDR bacteria was assed using well diffusion and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…wightiana and reported the anti-proliferative properties. The qualitative and quantitative profile of Cyathea sps secondary metabolites is reported and the hepatoprotective, anti-microbial and anti-cancer potential of C. gigantea are reported [17,29,34,[37][38][39][40]42]. But there is no report on UV-Vis and FTIR spectroscopic profile of Anemia schimperiana subsp.…”
Section: Introductionmentioning
confidence: 99%
“…wightiana and reported the anti-proliferative properties. The qualitative and quantitative profile of Cyathea sps secondary metabolites is reported and the hepatoprotective, anti-microbial and anti-cancer potential of C. gigantea are reported [17,29,34,[37][38][39][40]42]. But there is no report on UV-Vis and FTIR spectroscopic profile of Anemia schimperiana subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Tree ferns play an important role in human life due to their ornamental, food, and medical applications [14][15][16]. It has been shown that the extracts from the Cyathea genus plants have such properties as antimicrobial [17], larvicidal [18], phytotoxic [19], hepatoprotective [20], and antioxidant [21]. Thus, to fulfil the demand for the tree ferns, alternative ways for their propagation are increasingly being developed.…”
Section: Introductionmentioning
confidence: 99%